Privacy threats versus trust: a behavioral decision approach to social media disclosure intention - Zhu, Luhui; Zhang, Changfu; Omar, Bahiyah; Qi, Fei; Ji, Hongchao (Frontiers in Psychology, 2025)
IntroductionAs social media becomes a central platform for self-expression and communication, users are increasingly faced with the dilemma of disclosing personal information while managing privacy risks. This study explores how privacy-related factors, namely privacy invasion experiences, privacy fatigue, and privacy concerns, are associated with users’ intention to disclose on social media, with trust in social media serving as a mediating variable. Integrating behavioral decision theory and trust theory, the study aims to uncover the psychological mechanisms driving social media disclosure intention in a digital context.MethodsA quantitative survey was conducted with 787 participants to examine the proposed relationships. PLS-SEM was employed to test the hypothesized paths and mediating effects within the theoretical framework.ResultsThe results demonstrate that trust in social media is the most important predictor of social media disclosure intention, exceeding the negative impact of privacy-related factors. All three privacy-related variables negatively influence users’ intention to disclose, with privacy concerns showing the strongest negative effect. Trust in social media mediates the relationship between privacy invasion experiences and privacy concerns and social media disclosure intention. Furthermore, we found no significant relationship between privacy fatigue and trust in social media.DiscussionThe study extends existing theory by applying behavioral decision theory to the digital privacy domain and underscores the importance of trust in social media as a psychological bridge between privacy threats and social media disclosure intention.